OʻZBEKISTONNING BARQAROR RIVOJLANISH MAQSADLARIDA “YASHIL IQTISODIYOT”GA INVESTITSIYALARNI JALB QILISH IMKONIYATLARI OSHIRISH (Marketing Journal, 2026)
AbstractThe article reveals the prospects for attracting foreign and domestic investmentsin order to implement the tasks set out in the development strategy of Uzbekistan,increase the effectiveness of measures taken to ensure “green” and inclusive economicgrowth within the framework of the strategy of transition of the Republic of Uzbekistanto a “green” economy, further expand the use of renewable energy sources, and saveresources in all sectors of the economy.Keywords: green economy, green investment, green energy, foreign investors,green financing.